Prognostic value of forward flow indices in primary mitral regurgitation due to mitral valve prolapse - Elisabeth Petolat; Elisabeth Petolat; Alexis Theron; Noemie Resseguier; Cyprien Fabre; Giulia Norscini; Rita Badaoui; Gilbert Habib; Frederic Collart; Stéphane Zaffran; Alizée Porto; Jean-François Avierinos (Frontiers in Cardiovascular Medicine, 2023)
BackgroundDegenerative mitral regurgitation (DMR) due to mitral valve prolapse (MVP) is a common valve disease associated with significant morbidity and mortality. Timing for surgery is debated for asymptomatic patients without Class I indication, prompting the search for novel parameters of early left ventricular (LV) systolic dysfunction.AimsTo evaluate the prognostic impact of preoperative forward flow indices on the occurrence of post-operative LV systolic dysfunction.MethodsWe retrospectively included all consecutive patients with severe DMR due to MVP who underwent mitral valve repair between 2014 and 2019. LVOTTVI, forward stroke volume index, and forward LVEF were assessed as potential risk factors for LVEF <50% at 6 months post-operatively.ResultsA total of 198 patients were included: 154 patients (78%) were asymptomatic, and 46 patients (23%) had hypertension. The mean preoperative LVEF was 69 ± 9%. 35 patients (18%) had LVEF ≤ 60%, and 61 patients (31%) had LVESD ≥40 mm. The mean post-operative LVEF was 59 ± 9%, and 21 patients (11%) had post-operative LVEF<50%. Based on multivariable analysis, LVOTTVI was the strongest independent predictor of post-operative LV dysfunction after adjustment for age, sex, symptoms, LVEF, LV end systolic diameter, atrial fibrillation and left atrial volume index (0.75 [0.62–0.91], p < 0.01). The best sensitivity (81%) and specificity (63%) was obtained with LVOTTVI ≤15 cm based on ROC curve analysis.ConclusionLVOTTVI represents an independent marker of myocardial performance impairment in the presence of severe DMR. LVOTTVI could be an earlier marker than traditional echo parameters and aids in the optimization of the timing of surgery.